Development of online information system of agricultural science professionals and researchers in Southern Mindanao - Lim, Honeylet May Guinto (2006)
This online information system provides information of agricultural professionals as well as their researcher in Southern Mindanao. This system has three users, the system administrator, the registered professionals, and the guests. Professionals who want their profile to be uploaded in the database should register. Once they have received the confirmation email from the system administrator that their profile has been verified and uploaded, they may now upload more information about themselves and their studies. All professionals who are registered are automatically registered as a member of the agri forum. The agri form is a system feature which allows the registered professionals and the guests to communicate with each other by creating a topic and posting messages. Guests must register in the forum to be able to create topics and post messages. Through this system, agricultural researchers can be accessed from anywhere and anytime by potential end-users and enables geographically separated agricultural science professionals to scientifically collaborate with each other